PEMBUATAN MEDIA PROMOSI DESA BALONGSARI - Pradana, Trio Atang; Supratno, Setyo (DEVOSI, 2021)
The development of the website at this time has grown so fast due to the development of the internet infrastructure which is quite rapid. This has resulted in many industry players, educational institutions, health institutions and others using websites and other online-based applications as business and information delivery. The village government does not want to be left behind in providing excellent service to its citizens by providing information on the media website. The community service carried out introduced Balongsari Village as a tourist village with the target of promoting economic, social and cultural activities. The method used is in the form of counseling and website creation training. The continuity of this community service activity is in the form of a website created that is followed up by being managed by the local government to be used as a promotional media.